Color Image Analysis by Quaternion-Type Moments - Chen, Beijing; Shu, Huazhong; Coatrieux, Gouenou; Chen, Gang; Sun, Xingming; Coatrieux, Jean Louis (Journal of mathematical imaging and vision, 2015)
In this paper, by using the quaternion algebra, the conventional complex-type moments (CTMs) for gray-scale images are generalized to color images as quaternion-type moments (QTMs) in a holistic manner. We first provide a general formula of QTMs from which we derive a set of quaternion-valued QTM invariants (QTMIs) to image rotation, scale and translation transformations by eliminating the influence of transformation parameters. An efficient computation algorithm is also proposed so as to reduce computational complexity. The performance of the proposed QTMs and QTMIs are evaluated considering several application frameworks ranging from color image reconstruction, face recognition to image registration. We show they achieve better performance than CTMs and CTM invariants (CTMIs). We also discuss the choice of the unit pure quaternion influence with the help of experiments. ( i - j - k ) / 3 appears to be an optimal choice.